Endpoints in Phase II trials for advanced non-small cell lung cancer - Mandrekar, Sumithra J. (2010)
INTRODUCTION: We investigated the relationships between progression-free survival (PFS), response, confirmed response, and failure-free survival (FFS) with overall survival (OS) to assess their suitability as primary endpoints in phase II (P2) trials for advanced NSCLC. METHODS: Individual data of 284 patients from 4 P2 trials were pooled. Progression status and response were modeled as time dependent variables in a multivariable (adjusted for baseline age, gender, stage, and performance status) Cox proportional hazards (PH) model for OS, stratified by trial. Subsequently, Cox PH models were used to assess the impact of PFS, response, confirmed response and FFS on subsequent survival, using landmark analysis at 8, 12, 16, 20, and 24 weeks. Model discrimination was evaluated using the concordance (c) index. RESULTS: The overall median OS, PFS and FFS were 9.6, 3.7 and 2.8 months, and the response and confirmed response rates were 21% and 15% respectively. Both progression status and response as time dependent covariates were significantly associated with OS (p<0.0001; p=0.009). PFS and FFS at 12 weeks significantly predicted for subsequent survival with the strongest c-index and hazard ratio (HR) combination in landmark analyses (HR, c-index: PFS - 0.39, 0.67; FFS - 0.37, 0.67). The c-indices for response and confirmed response were low (0.59-0.60), indicating their inability to sufficiently discriminate subsequent patient survival outcomes. CONCLUSIONS: Failure-free survival or progression-free survival at 12 weeks is a stronger predictor of subsequent patient survival compared to tumor response, and should be routinely used as endpoints in phase II trials for advanced NSCLC.